MOLECULAR CHARACTERISATION OF A NOVEL NIGERIAN PLANT AS SYZYGIUM SPP OF THE MYRTACEAE FAMILY USING DNA BARCODING - Oduma, Sarah Ene; Ibrahim, Anna; Ahmed, Rashida; Muhammed, Abdullahi Abdulazeez (FUDMA JOURNAL OF SCIENCES, 2025)
This research focuses on the taxonomy and DNA barcoding of Syzygium guineense (S. guineense), commonly known as ‘water pear’ or ‘water berry’, a medicinal plant of great importance in Nigeria. Molecular characterisation is required to accurately identify medicinal plants from families known for complex taxonomy and a multitude of species. We used a dual approach combining taxonomical and molecular barcoding techniques. The plant specimen was initially identified by a taxonomist as S. guineense. Organoleptic and microscopic evaluations described the leaves as shiny green, ovate, 7–13 cm long, papery in texture, fragrant when crushed, with entire margins and obtuse apices. Microscopy revealed paracytic stomata, while chemomicroscopy confirmed the presence of cell wall materials and inclusions. Phytochemical screening indicated flavonoids, alkaloids, saponins, glycosides, and tannins, consistent with diagnostic features of Syzygium species. Molecular identification was performed using the Ribulose Bisphosphate Carboxylase (rbcl) gene marker. The rbcl gene is used as a DNA barcode for species identification and classification. Genomic DNA was extracted and amplified via end-point PCR, yielding a 542 bp fragment with 43.17% GC content, consistent with reported rbcL sequences in the Myrtaceae family. BLAST analysis revealed 100% query cover and 99.08% identity with multiple Syzygium species and other Myrtaceae members, confirming genus-level placement. However, the rbcL marker did not conclusively resolve the plant as S. guineense at the specie level. This finding highlights the limitations of relying solely on morphological and phytochemical traits for plant identification. Additional molecular markers are required to resolve closely related species with overlapping characteristics.
Keywords: DNA Barcoding; Pharmacognostic; Phytochemicals; Syzygium guineense; Taxonomy